Fundamentals of electromagnetic levitation engineering sustainability through efficiency - Sangster, Alan J. (London, United Kingdom The Institution of Engineering and Technology, 2012)
Electromagnetic levitation is commonly associated with transport applications, principally 'MagLev' trains. However the technology has many potential applications across engineering, particularly where there is a requirement to improve efficiency of electrical products and devices, propelled by the desire to minimise frictional and bearing losses and ohmic losses in conductors, which are the major causes of machine inefficiency. Fundamentals of Electromagnetic Levitation: Engineering sustainability through efficiency is an introductory text encompassing the enabling electrical technologies associated with magnetic levitation, electrostatic suspension, diamagnetic levitation and superconduction, high frequency magnetic levitation, high frequency electric suspension, and levitation using microwave pressure. It aims to make aspiring and existing electrical engineers aware of the efficiency implications of frictionless machines and hence of how important this may be in a post fossil fuel world in which the energy available from renewable sources is strictly limited.
Electronic reproduction.
Keywords: Magnetic suspension; Electric conductors; Levitation; Magnetics; Electronic books